Improve Science Learning Outcomes For Elementary School Students Through The Development Of Flipbook Media - Framz Hardiansyah; Mulyadi (Postgraduate, University of Mataram, 2022)
This development research aims to: (1) develop Flipbook learning media in science learning material for animal life cycles (metamorphosis), (2) the level of validity of Flipbook learning media, and (3) the effectiveness of Flipbook learning media. The trial subjects were 25 Class IV students and a teacher at SDN Poja II Sumenep. This research method uses the Research and Development (R&D) type ADDIE development model, which has five stages: analysis, design, development, implementation, and evaluation. The data collection instrument was in the form of a questionnaire given to media experts and material experts to see the validity of the developed media. The research design is a one-group pre-test post-test design with before-after experiments. The experts obtained an average score of 94.92% based on the assessment results, with an excellent assessment category. The average score of the teacher response assessment is 4.41, and the average student response assessment is 3.6 with the category of effectiveness, namely effective. From all validator responses, teacher responses, and student responses, in the development of Flipbook learning media in the Science class IV subject at SDN Poja II Sumenep, it was declared feasible to be used in the teaching and learning process.